Liquid Chromatography-Tandem Mass Spectrometry Method for the Determination of Trimetazidine in Human Plasma - Zou, Jianjun; Dai, Li; Wang, Guang Ji; Zhu, Yubing; Fan, Hongwei; Xiao, Da Wei (Arzneimittelforschung, 2008)
A sensitive liquid chromatography-tandem mass spectrometry (LC/MS/MS) method was developed and validated for the determination of trimetazidine (CAS 13171-25-0) in human plasma, using pseudoephedrine as internal standard (IS). Plasma samples were simply pretreated with methanol for deproteinization. The chromatographic separation was performed on a C18 column with a mobile phase of 3 mmol/L ammonium acetate solution-methanol (15:85, v/v) at a flow rate of 0.3 mL/min. The chromatographic separation was achieved in less than 3.2 min. The linearity was established over the concentration range of 1–100 ng/mL. Both intra- and inter-batch standard deviations were less than 9.5%. The method was successfully applied to study the relative bioavailability of trimetazidine hydrochloride tablets in healthy Chinese volunteers and the pharmacokinetic parameters of the reference and test tablets were compared.
Keywords: Antianginal drugs; CAS 13171-25-0; Trimetazidine, bioavailability, LC/MS/MS, pharmacokinetics